Impact of 16/8 time-restricted eating on body composition and lipolytic hormone regulation in female DanceSport dancers - Xinxin Li; Xian Guo; Yanbing Zhou; Guoxia Cao; Mengmeng Chen; Jinhao Mu (Journal of the International Society of Sports Nutrition)
Objective The aim of this study was to investigate the effect of a 16/8 time-restricted eating (TRE) program over 6 weeks on body composition and lipolytic hormone levels in female DanceSport dancers. Importantly, participants were not subject to any calorie restrictions during the study period.Methods A total of 20 female DanceSport dancers were recruited to participate in the randomized controlled trial. The participants were randomly assigned to either a time-restricted eating group (TRE, n = 10) or a control group (n = 10). The TRE group adhered to a 16/8 time-restricted eating protocol for a period of six weeks, consuming food within an eight-hour window (11:00–19:00) and fasting for 16 hours. The control group was instructed to maintain their usual dietary habits without any intervention. Body composition parameters, including body fat percentage (BF%), fat mass (FM), and fat-free mass (FFM), were measured before and after the intervention. Additionally, serum levels of epinephrine (E), norepinephrine (NE), adiponectin (ADPN), leptin (LEP), growth hormone (GH), insulin-like growth factor 1 (IGF-1), and blood lipid profiles (including total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C) and triglycerides (TG)) were assessed.Results After 6 weeks, the TRE group showed significant reductions in FM and BF% compared to baseline (p < 0.01). No significant changes were observed in body weight or FFM (p > 0.05). Regarding blood lipid profiles, HDL-C levels significantly increased in the TRE group (p < 0.05) following the 6-week intervention. In contrast, no significant changes were observed in TC, TG and LDL-C (p>0.05). Hormonal analysis revealed significant changes in the TRE group. Serum levels of epinephrine (E) and norepinephrine (NE) increased significantly following the intervention (p < 0.05), with E showing a particularly marked increase (p < 0.01). Additionally, serum adiponectin (ADPN) levels were significantly elevated (p < 0.05), while GH, IGF-1 and LEP levels did not show significant changes (p > 0.05). Group-by-time interactions were observed for FM (p < 0.05), BF% (p < 0.05), and E (p < 0.05). Comparisons of baseline and post-intervention dietary data indicated no significant changes in total calorie or macronutrient intake within either the TRE or control groups (p > 0.05).Conclusion Time-restricted eating without caloric restriction may offer a promising approach to regulating body composition and promoting lipid metabolism, especially for female DanceSport dancers where maintaining a lean body mass is critical. However, the long – term effects of this approach still warrant continued observation.